Constant comedy : how I started Comedy Central and lost my sense of humor : a memoir - Bell, Art (Ulysses Press, 2020)
Discover the riveting, hilarious true story of the birth of Comedy Central in what New York Times bestselling author, Dan Lyons, calls the "funniest behind-the-scenes memoir I've ever read, full of crazy characters, plot twists, and suspense." In 1988, a young, mid-level employee named Art Bell pitched a novel concept, a television channel focused 100% on just one thing, comedy, to the chairman of HBO. The station that would soon become Comedy Central, with celebrated programs like South Park, Chapelle's Show, The Daily Show, and The Colbert Report, was born. Constant Comedy takes readers behind the scenes into the comedy startup on its way to becoming one of the most successful and creative purveyors of popular culture in the United States. From disastrous pitch meetings with comedians to the discovery of talents like Bill Maher and Jon Stewart, this intimate biography peers behind the curtain and reveals what it's really like to work, struggle, and ultimately succeed at the cutting edge of show business.